Postnatal Dysregulation of Androgens in Extremely Preterm Male Infants - Nilsson, Anders K.; Söobom, Ulrika; Landin, Andreas; Andersson, Mats X.; Ryberg, Henrik; Pivodic, Aldina; Löfqvist, Chatarina; Sävman, Karin; Poutanen, Matti; Ohlsson, Claes; Hellström, Ann (Oxford University Press, 2025)
Context: Neurodevelopmental impairments are common among survivors of extremely preterm birth, particularly in males. Hyperactivation of the hypothalamic-pituitary-gonadal (HPG) axis has been suggested as an underlying cause, but this has been poorly investigated.
Objective: Establish levels and temporal changes in circulating androgens in extremely preterm infant males.
Methods: Observational cohort study analyzing cord blood serum (n = 25) and postnatal plasma (n = 13) collected from day 0 until week 11 from infant males born at 22.8-27.9 weeks gestational age. Testosterone and dihydrotestosterone (DHT) were determined using gas chromatography mass spectrometry, sex hormone-binding globulin (SHBG) with an enzyme-linked immunosorbent assay, and follicle-stimulating hormone (FSH) and luteinizing hormone (LH) with the Luminex xMAP multiplex assay.
Results: Testosterone and DHT levels were higher on day 0 (median 4.27 and 0.30 ng/mL) than in cord blood (0.15 and 0.01 ng/mL) (P < .001 for both). Levels of the hormones then declined rapidly until day 5 (median 0.16 and 0.12 ng/mL), then remained relatively constant throughout the study period. Median levels of testosterone and DHT across the whole study period were approximately 6-fold higher than reported in utero levels. FSH and LH showed similar postnatal patterns as the androgens. SHBG steadily increased over time, and, as a result, the fraction of bioavailable testosterone declined with infant postnatal age.
Conclusion: The HPG axis is activated immediately after birth in extremely preterm infant males, resulting in an androgen pulse occurring several months earlier than during a normal pregnancy. The long-term implications of high androgen exposure during a sensitive neurodevelopmental period warrant further studies.